A new genus of Asterocheridae (Copepoda: Siphonostomatoida) ectoassociate of the ascidian Eudistoma vannamei Millar, 1977 (Polycitoridae) from Brazil - Johnsson, Rodrigo; Bahia, Cristiano; Neves, Elizabeth (Zootaxa, 2016)
Asterocheres Boeck, 1860 is the largest genus of the siphonostomatoid copepod family Asterocheridae, containing 63 valid species. The genus is known for its symbiotic relationships with many marine invertebrate taxa, especially sponges, cnidarians, bryozoans, and echinoderms. Recent studies have restricted the diagnosis of this genus. Consequently, many species are now considered as species inquirendae. The present paper describes a new species living externally on the tunic of Eudistoma vannamei Millar, 1977, an endemic ascidian from Brazil. As the new species does not fit Asterocheres in the strict sense, a new genus is erected to accommodate it. Setacheres gen. nov. is characterized by its possession of two distal setae on the third endopodal segment of P3, thus differing from the distal seta and spine pattern that is deemed as diagnostic of Asterocheres. A revision and comparison of Asterocheres´ species inquirendae revealed eight species sharing the same generic characteristics and were thus reallocated as members of the new genus.